Security Instruments Governed by Polish Law in International Financing Transactions - Lorenc, Marcin (Journal of Finance and Financial Law, 2024)
The purpose of the article. As noted recently, an increased number of financing transactions through financing documents with international elements has been reported. We are referring in particular to facility agreements prepared under the LMA standard governed by the English law and the objects of potential providers of facility security located in multiple jurisdictions, e.g., 'subsidiaries' acting as guarantors or additional debtors, but sometimes also as borrowers. The multiplicity of jurisdictions poses a challenge to the lender's advisers, but also to the principal borrower, as to which security instruments to use in each jurisdiction depending on where the security interest is located. This article aims to provide an overview of the most commonly used types of security under the Polish law to secure loan agreements in jurisdictions other than the Polish one. In addition, the author has made an assessment that may be helpful to non-Polish practitioners in selecting the appropriate security for a debt. The main objective was to acquaint those unfamiliar ones with the Polish law with the standards of the Polish debt security law. The main hypothesis is that the Polish security provides certainty to foreign institutions granting facilities where a Polish entity is involved as a security provider. Methodology. The article provides a comprehensive review of the literature on Polish legal security for facility receivables granted under a foreign law (including legal acts). The applied methods include the hermeneutic method, the comparative method and the method of analysis and synthesis. Results of the research. On the basis of the conducted research it was found that Polish collateral documents are sufficient to secure receivables arising from facilities governed by a foreign law. The main hypothesis appears to have been proven. In addition, on the basis of the research it was proved that Polish security documents, due to their legal significance, should constitute an incentive for foreign financial institutions to take up in Poland. The conclusion is that the Polish security law is wealthy in terms of instruments allowing for certainty of trading between international institutions.